Catheter Associated Urinary Tract Infection: Characterization of Bacterial Pathogens and their Antimicrobial Susceptibility Pattern at Two Major Tertiary Care Hospitals - Gul, Amina (International Journal of Pathology, 2022)
Background: Catheter Associated Urinary Tract Infection (CAUTI) remains a leading cause of Hospital Acquired Infections (HAIs), leading to increased morbidity, mortality and financial impact on healthcare delivery systems. Objectives: To isolate bacterial pathogens from urine specimens of patients with CAUTI and determine their Antimicrobial susceptibility pattern. Materials and Methods: Urine samples were cultured on blood agar, MacConkey agar, and cysteine lactose electrolyte deficient agar. Species identification was achieved using gram stain and biochemical tests. Resistance profile of each isolate was recorded using Kirby Bauer disc diffusion method as per Clinical and Laboratory Standard Institute (CLSI) M-100 version 2021. Results: Gram Negative bacteria accounted for 79% of all the CAUTIs with Escherichia coli (54%) as a major pathogen. Enterococci (19%) were predominant among gram positive bacteria (21%). While E. coli isolates revealed 100% resistance to ampicillin and co-amoxiclav, resistance to cefoperazone-sulbactam was observed in 75% and 100% of E. coli and Citrobacter freundii respectively. E. coli, Enterococci and Klebsiella pneumoniae were found resistant to fosfomycin in 1%, 17% and 36% of the isolates respectively. E coli resistance to nitrofurantoin was observed as 23%. In total 50% of the K. pneumonia and C. freundii isolates were resistant to nitrofurantoin. Among K. pneumoniae isolates 82% were resistant to meropenem and 55% were resistant to piperacillin tazobactam. Vancomycin resistant enterococci were observed only in 6% of CAUTIs. Conclusion: Multidrug resistant E. coli, Klebsiella and Enterococci are leading pathogens in CAUTIs. Nitrofurantoin, aminoglycosides, carbapenems and fosfomycin has good invitro activity against bacterial pathogens isolated from patients with CAUTI. Prior knowledge of bacterial etiology and its associated AMR pattern could help clinicians for selection of appropriate antimicrobial therapy